Development and Validation of Ethical Awareness Scale among University Students - Kumolohadi, Retno; Mangunsong, Frieda; Suleeman, Julia (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2021)
Plagiarism, intolerance, and sexual harassment highlight the assessment of university students’ ethical awareness as essential measure. The study aims to develop and validate an ethical awareness scale by constructing a measuring instrument based on Yeung and Keup’s (2009) preliminary research, using open ended questionnaire and focus group discussions, expert judgement, and legibility test. 251 students were recruited through convenience sampling. The results of psychometric testing using exploratory factor analysis indicate that the 12-item scale is valid in terms of construct validity. The Kaiser Meyer Olkin test showed a score of 0.865, with a Bartlett’ s Sphericity test value of 1.240, df = 66 and p = 0.000, and the factor loading ranged from 0.409 to 0.814. Total variance explained by this scale is 46.827%, in which academic and social factors contribute to 39.001% of variance, while information technology contributes to 7.826% of variance. Reliability testing using Cronbach's Alpha yielded a coefficient value of α = 0.874. The implications of this study include the necessities for further development of the instrument to specifically measure information technology factor, to conduct confirmatory factor analysis with other students, and to modify the scale based on participants’ different characteristics. This scale can also be used to determine the effectiveness of ethics outreach programs.